Religious, Ethical And Legal Considerations In End-of-life Issues: Fundamental Requisites For Medical Decision Making - Puteri Nemie Jahn Kassim; Fadhlina Alias (Springer, 2024)
Religion and spirituality have always played a major and intervening role in a person’s life and health matters. With the influential development of patient autonomy and the right to self-determination, a patient’s religious affiliation constitutes a key component in medical decision making. This is particularly pertinent in issues involving end-of-life decisions such as withdrawing and withholding treatment, medical futility, nutritional feeding and do-not-resuscitate orders. These issues affect not only the patient’s values and beliefs, but also the family unit and members of the medical profession. The law also plays an intervening role in resolving conflicts between the sanctity of life and quality of life that are very much pronounced in this aspect of healthcare. Thus, the medical profession in dealing with the inherent ethical and legal dilemmas needs to be sensitive not only to patients’ varying religious beliefs and cultural values, but also to the developing legal and ethical standards as well. There is a need for the medical profession to be guided on the ethical obligations, legal demands and religious expectations prior to handling difficult end-of-life decisions. The development of comprehensive ethical codes in congruence with developing legal standards may offer clear guidance to the medical profession in making sound medical decisions.